2007
DOI: 10.1002/art.23186
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular accumulation of plasmacytoid dendritic cells in active lupus nephritis: Role of interleukin‐18

Abstract: Objective. Defective circulating dendritic cells (DCs) have been described in systemic lupus erythematosus (SLE) and correlated with high levels of interferon-␣ (IFN␣). DCs are differentiated as being either myeloid or plasmacytoid, according to chemokine expression and the tendency to migrate toward inflamed tissue. We investigated the potential role of interleukin-18 (IL-18) in driving the glomerular migration of DCs in lupus nephritis (LN) and in affecting the ability of DCs to induce an imbalance in the Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
150
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(156 citation statements)
references
References 30 publications
5
150
1
Order By: Relevance
“…Our hypothesis may be supported by studies recently conducted by Tucci et al (2008), who reported increased production of IL-18 in patients with lupus nephritis [41]. Moreover, they found that patients with severe lupus nephritis exhibit a high accumulation of IL-18 within glomeruli [41].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our hypothesis may be supported by studies recently conducted by Tucci et al (2008), who reported increased production of IL-18 in patients with lupus nephritis [41]. Moreover, they found that patients with severe lupus nephritis exhibit a high accumulation of IL-18 within glomeruli [41].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, they found that patients with severe lupus nephritis exhibit a high accumulation of IL-18 within glomeruli [41]. They suggested that IL-18 is biosynthesized by macrophages within nephritic glomeruli, and this cytokine may chemoattract plasmacytoid dendritic cells to kidney glomeruli, leading to renal damage [41]. Wong et al (2002) also reported elevated production of IL-18 in SLE patients with renal disease [42].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the decreased SLAM expression on circulating pDCs in SLE could be that SLE IC-activated cells migrate from the circulation to inflamed tissues. Such redistribution from blood to tissues of pDCs that produce IFN-a was also described in SLE (42,43) and might explain our observation. On SLE NK cells, decreased expression of CD229 on CD56 dim NK cells and increased expression of CD319 and CD48 on CD56 bright NK cells were observed.…”
Section: Altered Expression Of Cd319 and Cd229 On Pdcs And Nk Cells Fsupporting
confidence: 85%
“…The increased glomerular expression of IL-18 in established human LN was also reported by different groups. 7,16,33,41 To our knowledge, we are the first group to report expression of IL-18 in renal tissue of subclinical LN.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, a relationship between tubular IL-18 expression and renal disease activity has been demonstrated. 13,15 Tucci et al 16 in 2008 demonstrated decrease in peripheral plasmacytoid dendritic cells (DCs), which expressed IL-18 receptor, in patients with LN and they suggested that the high level of expression of IL-18 receptor by peripheral plasmacytoid DCs helps the DCs to relocate within glomeruli under IL-18 stimulation and promote renal damage. Furthermore, Hatef et al 17 in 2013 showed a correlation between IL-18 and serum Fas in patients with LN being highly significant in patients with severe SLE than those with milder disease.…”
mentioning
confidence: 99%